Preparation method of In2O3-Cu-Cu2O ternary heterojunction catalyst

By using a hydrothermal crystallization and calcination process with an ethylenediamine-ethylene glycol solvent system and controlling the amount of deionized water added, an In2O3-Cu-Cu2O ternary heterojunction was successfully constructed on a Cu2O substrate. This solved the problems of high recombination rate and weak oxidation ability of Cu2O-based photocatalytic materials, and achieved efficient carrier separation and improved oxidation ability.

CN120961164BActive Publication Date: 2025-12-12SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511500522.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-12-12
Estimated Expiration
2045-10-21

AI Technical Summary

Technical Problem

Existing Cu2O-based photocatalytic materials suffer from problems such as high recombination rate of photogenerated carriers, weak oxidation ability, and severe photocorrosion. Furthermore, existing methods are insufficient to achieve precise control of the ratio of the three phases In2O3, Cu, and Cu2O, as well as the interface structure.

Method used

A ternary heterojunction of In2O3-Cu-Cu2O was formed by hydrothermal crystallization at room temperature and calcination in an inert atmosphere using an ethylenediamine-ethylene glycol diolamine solvent system. The ratio and interface structure of Cu0, Cu2O and In2O3 were controlled by adjusting the amount of deionized water added.

Benefits of technology

In-situ generation of metallic Cu on Cu2O substrate and uniform composite of In2O3 were achieved. The three-phase ratio and interface structure were precisely controlled, which improved the carrier separation efficiency and oxidation capacity of the photocatalyst and ensured batch repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961164B_ABST
    Figure CN120961164B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an In2O3-Cu-Cu2O ternary heterojunction catalyst. The method comprises the following steps: dissolving indium chloride tetrahydrate in ethylenediamine-glycol (volume ratio 1:20-1:30) binary glycol amine mixed solvent to obtain a homogeneous solution at room temperature and normal pressure; then, the solution is transferred to a hydrothermal kettle, different volumes of deionized water and Cu2O powder are added, and hydrothermal crystallization is carried out at 160-200 DEG C for 10-14 h; the obtained precipitate is subjected to centrifugal separation, water washing-alcohol washing alternately 2-3 times, vacuum drying at 60 DEG C for 5-7 h, and then calcination is carried out under N2 atmosphere at a temperature increasing rate of 3-5 DEG C / min to 600±10 DEG C for 3 h, and the target product is obtained after furnace cooling. By adjusting the addition amount of deionized water, the mass ratio of In2O3, Cu and Cu2O three phases can be continuously controlled, and the controllable preparation from "rich copper" to "rich cuprous oxide" to "stable ternary" can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of nanomaterials, and particularly relates to a preparation method of an In2O3-Cu-Cu2O ternary heterojunction catalyst. BACKGROUND

[0002] Cuprous oxide (Cu2O) as a typical p-type semiconductor has attracted extensive attention in the field of photocatalysis due to its band gap of about 2.0-2.2 eV and visible light absorption capability. However, the single Cu2O material has a problem of fast recombination rate of photo-generated electron-hole pairs, which leads to an unsatisfactory quantum efficiency in actual application.

[0003] In order to improve the carrier separation efficiency, the prior art proposes a strategy of constructing a heterojunction. One of them is to load metal copper (Cu 0 ) on the surface of Cu2O to form a Cu / Cu2O heterojunction. The Schottky barrier formed by the metal-semiconductor contact can effectively promote the migration and separation of photo-generated electrons. However, the oxidation capacity of this binary system is mainly determined by the valence band position of Cu2O, which is limited in reactions requiring strong oxidizing holes.

[0004] In order to further improve the oxidation capacity of the system, researchers try to combine Cu2O with a wide-bandgap n-type semiconductor, which can theoretically construct a p-n heterojunction to enhance the built-in electric field, and use the deeper valence band position of In2O3 to obtain a higher oxidation potential.

[0005] However, a single binary combination strategy is difficult to achieve efficient electron conduction and high oxidation potential simultaneously. In order to construct a new In2O3-Cu-Cu2O ternary heterojunction to integrate the electronic intermediate function of metal Cu and the high oxidation capacity of In2O3, a core technical challenge will be faced: how to realize the in-situ generation of metal Cu and the uniform combination of In2O3 on the Cu2O substrate at the same time, and accurately control the proportion and interface structure of the three phases. When the existing method is applied to this new system, it is expected that the ternary heterojunction with regular structure and reproducible performance will be difficult to achieve due to the complexity of the process and the difficulty of synergistic regulation.

[0006] Therefore, it is of great significance to develop a preparation method which is simple in process, can in-situ construct and accurately control the proportion and interface structure of In2O3, Cu and Cu2O, for promoting the basic research and practical application of this kind of multi-component heterojunction catalyst. SUMMARY

[0007] The present application aims at the problems of high photogenerated carrier recombination rate, weak oxidation ability and serious photo corrosion of the existing Cu2O-based photocatalytic material, and provides a preparation method of an In2O3-Cu-Cu2O ternary heterojunction photocatalyst which is simple in process, mild in conditions and scalable in production. Through the process of "ethylenediamine-ethylene glycol glycolamine solvent system-hydrothermal crystallization-inert atmosphere calcination", Cu 0 The electron channel and the In2O3 high oxidation potential unit.

[0008] To achieve the above-mentioned purposes, the technical solutions of the present application are as follows:

[0009] A preparation method of an In2O3-Cu-Cu2O ternary heterojunction photocatalyst, comprising the following steps:

[0010] (1) Under room temperature and normal pressure conditions, a metered amount of indium chloride tetrahydrate (InCl3·4H2O) is dispersed in a binary glycolamine mixed solvent composed of ethylenediamine and ethylene glycol, and continuous stirring is performed until a clear homogeneous solution is formed, which is denoted as solution A;

[0011] (2) The solution A obtained in step (1) is transferred to a hydrothermal reaction kettle with a polytetrafluoroethylene lining, deionized water and Cu2O powder are sequentially added, and after sealing, a suspension B is obtained;

[0012] (3) The reaction kettle in step (2) is placed in a vacuum oven, and hydrothermal crystallization reaction is carried out at a constant temperature; after the reaction is completed, natural cooling to room temperature is carried out, and a purple suspension C is obtained;

[0013] (4) The suspension C obtained in step (3) is centrifuged, and the supernatant is discarded; then the precipitate is transferred to a vacuum drying box for drying, and a red-brown precursor powder is obtained;

[0014] (5) Under the protection of an inert atmosphere, the precursor obtained in step (4) is placed in a tube furnace for calcination, and then cooled to room temperature, and the target product, an In2O3-Cu-Cu2O ternary heterojunction catalyst, is obtained.

[0015] Preferably, in step (1), the volume ratio of ethylenediamine to ethylene glycol is 1:20-1:30; and the stirring time for forming a homogeneous solution is 20-40 min.

[0016] Preferably, in step (2), the volume ratio of added deionized water to ethylenediamine is 80:3-400:3.

[0017] Preferably, in step (3), the hydrothermal crystallization reaction conditions are as follows: 160-200 ℃ for 10-14 h.

[0018] Preferably, the centrifugal speed in step (4) is 4000-6000 rpm, the centrifugal time is 2-5 min, and the washing is performed by using deionized water and anhydrous ethanol alternately for 2-3 times each; the drying temperature in the vacuum oven is 60 DEG C, and the drying time is 5-7 h.

[0019] Preferably, in step (5), the inert gas is selected from nitrogen or argon; the heating rate is 3-5 DEG C / min, the calcination temperature is 600 DEG C + / - 10 DEG C, the holding time for calcination is 2-4 h, and the furnace is cooled to room temperature after the holding time ends.

[0020] Compared with the prior art, the present application has the beneficial effects that:

[0021] By using the single variable of "deionized water addition amount", the reduction depth of Cu2O and Cu 0 in the room temperature-normal pressure hydrothermal system can be accurately controlled: when 0 mL, the reduction ability of ethylenediamine is the strongest, the XRD semi-quantitative analysis shows that the proportion of Cu 0 is more than 70%, and the content of Cu2O is less; when the volume ratio of deionized water to ethylenediamine is 80:3-160:3, the water molecules and ethylenediamine compete for coordination, the reduction potential gradually decreases, the content of Cu 0 decreases from 65% to 15%, and the content of Cu2O rebounds; when the volume ratio of deionized water to ethylenediamine exceeds 160:3, the water amount is sufficient to saturate the coordination sites, the reduction tends to be limited, and the proportions of Cu 0 , Cu2O and In2O3 remain stable, realizing the "water amount-proportion" platform area and ensuring batch repeatability.

[0022] The essence is that the addition amount of deionized water directly determines the volume ratio of deionized water to ethylenediamine, thereby changing the competitive coordination ability of the two in the reaction system. When the water amount is small, the relative concentration of ethylenediamine is high, the strong coordination and reduction property dominates, and a large amount of Cu 0 is generated; with the increase of water amount, the water molecules compete with ethylenediamine for the coordination sites of metal ions, and dilute the effective concentration of ethylenediamine, which significantly inhibits the reduction ability of ethylenediamine, so that Cu2O can be preserved. Therefore, controlling the addition amount of water is essentially controlling the balance of the key competitive coordination relationship between water / ethylenediamine.

[0023] Therefore, by adjusting the addition amount of deionized water, the continuous switching between "rich copper-rich cuprous oxide-stable ternary" can be realized, the additional reducing agent or inert gas partial pressure adjustment is avoided, and the customized precursor is provided for the subsequent photocatalytic system with different oxidation / reduction requirements.

[0024] Reaction mechanism

[0025] In the ethylenediamine-ethylene glycol mixed solvent, ethylenediamine acts as a strong coordination agent, coordinates with In 3+Forming stable [In(en)3] 3+ The complex controls the hydrolysis and precipitation rate of the indium source. During the hydrothermal process, the complex gradually decomposes, releasing In 3 ⁺ which reacts with OH⁻ in the system to form In(OH)3 intermediate, and finally dehydrates to In2O3 in the calcination step.

[0026] At the same time, ethylenediamine has a mild reducing effect on the surface of the introduced Cu2O powder, which can reduce part of Cu⁺ to metal Cu 0 , forming Cu nanoparticles in situ. The amount of deionized water added is the key to realizing the controllable preparation of this method: when the amount of water is small, the reducing property of ethylenediamine dominates, resulting in a higher Cu 0 generation ratio; as the amount of water increases, water molecules compete for coordination sites with ethylenediamine, and the concentration of the reducing agent is diluted, so that the reducing ability of ethylenediamine is inhibited, and Cu2O is largely retained.

[0027] Finally, through the "hydrothermal-calcination" process, the In2O3-Cu-Cu2O ternary heterojunction structure is successfully constructed on the Cu2O substrate, with metal Cu as the electronic bridging channel and In2O3 as the high-potential oxidation unit. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 X-ray diffraction (XRD) patterns of the In2O3-Cu-Cu2O ternary heterojunction catalysts prepared for Examples 1-5 and Comparative Example 1.

[0029] Figure 2 XRD mass fraction pie charts of the In2O3-Cu-Cu2O ternary heterojunction catalysts prepared for Examples 1-5 and Comparative Example 1.

[0030] Figure 3 Scanning electron microscope images and element Mapping results of the In2O3-Cu-Cu2O ternary heterojunction catalysts prepared for Examples 1-3 and Comparative Example 1. Figure 3 Scanning electron microscope images and element Mapping results of the In2O3-Cu-Cu2O ternary heterojunction catalysts prepared for Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical solutions of the present application will be described below in conjunction with the data in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of the present application.

[0032] It should be noted that the professional terms used in the present application are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present application can be purchased on the market or prepared by existing methods.

[0033] One of the key control parameters of the method of the present application is the volume ratio of the added deionized water to the volume of ethylenediamine in the system. By adjusting this ratio, the competitive coordination behavior of water molecules and ethylenediamine to metal precursors can be precisely controlled, thereby realizing continuous regulation of the three-phase ratio of Cu, Cu2O and In2O3 in the final product.

[0034] Example 1

[0035] (1) At room temperature and normal pressure, 0.586 g of InCl3·4H2O was placed in a 50 mL beaker, and 0.75 mL of ethylenediamine and 19.25 mL of ethylene glycol (volume ratio 1:25) were added in sequence, and magnetic stirring was performed for 30 min until a colorless clear homogeneous solution was formed, which was denoted as solution A;

[0036] (2) Solution A was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel hydrothermal kettle, 20 mL of deionized water and 1.41 g of Cu2O powder were added, and it was immediately sealed to obtain suspension B;

[0037] (3) The hydrothermal kettle was placed in a vacuum oven, heated to 180 ℃ and kept at this temperature for 12 h; after the reaction was completed, it was naturally cooled to room temperature to obtain purple suspension C;

[0038] (4) Suspension C was centrifuged at 5000 rpm for 2 min, and the supernatant was discarded; the precipitate was washed with deionized water and anhydrous ethanol each for 2 times (10 mL each time), and then vacuum dried at 60 ℃ for 5 h to obtain a red-brown precursor powder;

[0039] (5) The precursor was laid flat in a porcelain boat and placed in a tube furnace, and heated to 600 ℃ at 5 ℃ / min under N2 atmosphere (200 mL / min), and then cooled with the furnace after keeping at this temperature for 3 h to obtain the target product, denoted as Cat-20.

[0040] Example 2

[0041] (1) At room temperature and normal pressure, 0.586 g of InCl3·4H2O was placed in a 50 mL beaker, and 0.75 mL of ethylenediamine and 19.25 mL of ethylene glycol (volume ratio 1:25) were added in sequence, and magnetic stirring was performed for 30 min until a colorless clear homogeneous solution was formed, which was denoted as solution A;

[0042] (2) Solution A was transferred into a 150 mL Teflon-lined stainless steel autoclave, 40 mL deionized water and 1.41 g Cu2O powder were added, and the autoclave was immediately sealed to obtain suspension B;

[0043] (3) The autoclave was placed in a vacuum oven, and the temperature was raised to 180 °C and kept constant for 12 h. After the reaction was completed, it was naturally cooled to room temperature to obtain purple suspension C;

[0044] (4) Suspension C was centrifuged at 5000 rpm for 3 min, and the supernatant was discarded. The precipitate was washed with deionized water and anhydrous ethanol for 2 times (10 mL each time) in turn, and then vacuum dried at 60 °C for 5 h to obtain red-brown precursor powder;

[0045] (5) The precursor was placed in a porcelain boat and put into a tube furnace. The temperature was raised to 600 °C at a rate of 5 °C / min under N2 atmosphere (200 mL / min), and the furnace was kept for 3 h and then cooled down to obtain the target product, which was recorded as Cat-40.

[0046] Example 3

[0047] (1) At room temperature and normal pressure, 0.586 g of InCl3·4H2O was placed in a 50 mL beaker, and 0.75 mL of ethylenediamine and 19.25 mL of ethylene glycol (volume ratio 1:25) were added in turn. The solution was stirred magnetically for 20 min until a colorless clear homogeneous solution was formed, which was recorded as solution A;

[0048] (2) Solution A was transferred into a 150 mL Teflon-lined stainless steel autoclave, 60 mL deionized water and 1.41 g Cu2O powder were added, and the autoclave was immediately sealed to obtain suspension B;

[0049] (3) The autoclave was placed in a vacuum oven, and the temperature was raised to 180 °C and kept constant for 12 h. After the reaction was completed, it was naturally cooled to room temperature to obtain purple suspension C;

[0050] (4) Suspension C was centrifuged at 5000 rpm for 4 min, and the supernatant was discarded. The precipitate was washed with deionized water and anhydrous ethanol for 2 times (10 mL each time) in turn, and then vacuum dried at 60 °C for 6 h to obtain red-brown precursor powder;

[0051] (5) The precursor was placed in a porcelain boat and put into a tube furnace. The temperature was raised to 600 °C at a rate of 5 °C / min under N2 atmosphere (200 mL / min), and the furnace was kept for 3 h and then cooled down to obtain the target product, which was recorded as Cat-60.

[0052] Example 4

[0053] (1) At room temperature and normal pressure, 0.586 g of InCl3·4H2O was placed in a 50 mL beaker, and 0.75 mL of ethylenediamine and 15 mL of ethylene glycol (volume ratio 1:20) were added in sequence, and magnetic stirring was performed for 20 min until a colorless and clear homogeneous solution was formed, which was recorded as solution A;

[0054] (2) Solution A was transferred to a 150 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, 80 mL of deionized water and 1.41 g of Cu2O powder were added, no additional water was added, and it was immediately sealed to obtain suspension B;

[0055] (3) The hydrothermal kettle was placed in a vacuum oven, and the temperature was raised to 160°C and kept constant for 12 h; after the reaction was completed, it was naturally cooled to room temperature to obtain purple suspension C;

[0056] (4) Suspension C was centrifuged at 4000 rpm for 5 min, and the supernatant was discarded; the precipitate was washed with deionized water and anhydrous ethanol for 2 times (10 mL each time) in sequence, and then vacuum dried at 60°C for 7 h to obtain a red-brown precursor powder;

[0057] (5) The precursor was placed in a porcelain boat and placed in a tube furnace, and heated to 590°C at 3°C / min under N2 atmosphere (200 mL / min), and then cooled with the furnace after holding for 3 h to obtain the target product, which was recorded as Cat-80.

[0058] Example 5

[0059] (1) At room temperature and normal pressure, 0.586 g of InCl3·4H2O was placed in a 50 mL beaker, and 0.75 mL of ethylenediamine and 15 mL of ethylene glycol (volume ratio 1:20) were added in sequence, and magnetic stirring was performed for 20 min until a colorless and clear homogeneous solution was formed, which was recorded as solution A;

[0060] (2) Solution A was transferred to a 150 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, 80 mL of deionized water and 1.41 g of Cu2O powder were added, no additional water was added, and it was immediately sealed to obtain suspension B;

[0061] (3) The hydrothermal kettle was placed in a vacuum oven, and the temperature was raised to 160°C and kept constant for 12 h; after the reaction was completed, it was naturally cooled to room temperature to obtain purple suspension C;

[0062] (4) Suspension C was centrifuged at 4000 rpm for 5 min, and the supernatant was discarded; the precipitate was washed with deionized water and anhydrous ethanol for 2 times (10 mL each time) in sequence, and then vacuum dried at 60°C for 7 h to obtain a red-brown precursor powder;

[0063] (5) The precursor was laid in a porcelain boat and put into a tube furnace, and then heated to 610 ℃ at a rate of 4 ℃ / min under an Ar atmosphere (200 mL / min), and cooled with the furnace after being kept for 3 h to obtain the target product, recorded as Cat-100.

[0064] Comparative Example 1

[0065] (1) 0.586 g of InCl3·4H2O was placed in a 50 mL beaker at room temperature and under normal pressure, and then 0.75 mL of ethylenediamine and 19.25 mL of ethylene glycol (volume ratio 1:25) were added in sequence, and the mixture was magnetically stirred for 30 min until a colorless and clear homogeneous solution was formed, recorded as solution A;

[0066] (2) Solution A was transferred to a 150 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, 1.41 g of Cu2O powder was added, and no additional water was added, and then the kettle was immediately sealed to obtain suspension B;

[0067] (3) The hydrothermal kettle was placed in a vacuum oven, and heated to 180 ℃ and kept at this temperature for 12 h; after the reaction was completed, the kettle was naturally cooled to room temperature to obtain purple suspension C;

[0068] (4) Suspension C was centrifuged at 5000 rpm for 3 min, and the supernatant was discarded; the precipitate was washed with deionized water and anhydrous ethanol for 2 times (10 mL each time) in sequence, and then vacuum dried at 60 ℃ for 6 h to obtain a red-brown precursor powder;

[0069] (5) The precursor was laid in a porcelain boat and put into a tube furnace, and then heated to 610 ℃ at a rate of 4 ℃ / min under an Ar atmosphere (200 mL / min), and cooled with the furnace after being kept for 3 h to obtain the target product, recorded as Cat-100.

[0070] Observation Figure 1 The In2O3-Cu-Cu2O ternary heterojunction catalyst prepared in the present application contains characteristic peaks belonging to Cu2O, Cu 0 and In2O3, which indicates that the In2O3-Cu-Cu2O ternary composite material is successfully prepared.

[0071] Observation Figure 2 It can be seen that with the increase of the amount of deionized water from 0 mL to 60 mL, the mass fraction of each crystal phase in the In2O3-Cu-Cu2O ternary heterojunction obtained in the present application shows a regular change:

[0072] (1) When the amount of water is 0 mL (Comparative Example 1), the XRD semi-quantitative analysis shows that Cu 074.1 wt%, Cu2O 10.7 wt%, In2O3 15.1 wt%, indicating that the reduction of ethylenediamine is dominant, and the copper-based components are mainly in the form of elemental substance.

[0073] (2) When the water amount is 20 mL (Example 1), Cu 0 decreased to 66.7 wt%, Cu2O increased to 15.0 wt%, and In2O3 increased to 18.2 wt%, and the degree of reduction was weakened.

[0074] (3) When the water amount is 40 mL (Example 2), Cu 0 content decreased to 16.1 wt%, Cu2O increased to 70.2 wt%, and In2O3 stabilized at 13.7 wt%, and cuprous oxide became the main phase.

[0075] (4) When the water amount is 60-100 mL (Examples 3-5), the mass fraction of each phase is similar to that under the condition of 40 mL (Cu 0 content is 15.0 wt%, Cu2O content is 71.5 wt%, and In2O3 content is 13.5 wt%), indicating that when the amount of deionized water added reaches 40 mL and above, the composition of the three phases tends to be stable, and further increasing the water amount has no significant effect on the phase composition.

[0076] Observation Figure 3 It can be seen that the amount of water added directly determines the morphology evolution and phase distribution of Cu2O-based catalysts:

[0077] When the water addition amount is 0 mL (Comparative Example 1), the system lacks water phase buffer, and the reduction potential of ethylenediamine increases sharply, the Cu2O skeleton is rapidly reduced, and the skeleton is broken to form irregular fragments; at the same time, the free Cu 0 and In2O3 nanoparticles randomly embed the surface of the fragments, forming a Cu / Cu2O / In2O3 three-phase disordered stacking structure, and EDS confirms that Cu and In signals are uniformly distributed in the entire fragment area.

[0078] When the water addition amount is increased to 20 mL (Example 1), the water phase part moderates the reduction intensity of ethylenediamine, and the Cu2O main body is preserved; however, the local high reduction microzone still promotes the dissolution of part of the vertex edges to Cu 0 . EDS element Mapping results further show that In2O3 is deposited on the interface between spherical Cu 0 and Cu2O matrix, forming an In2O3-Cu-Cu2O heterojunction.

[0079] When the water addition amount is 40 mL and 60 mL respectively (Examples 2, 3), the excess water phase significantly inhibits the reduction kinetics of ethylenediamine, and the Cu2O body remains intact, and In2O3 grows in a filamentous structure on the surface of Cu2O. The corresponding EDS results confirm that In and Cu signals only appear on the surface of Cu2O.

[0080] Comparative Example 1 (Cat-0) causes the Cu2O skeleton to break due to the absence of deionized water, and the three phases are randomly stacked without forming a regular heterojunction; and Examples 1-5 successfully construct the In2O3-Cu-Cu2O ternary heterojunction by adjusting the water volume, and as the water volume increases, the retention of Cu2O improves and the structure tends to be stable.

[0081] The above results clearly verify that the relative content of In2O3-Cu-Cu2O can be continuously controlled by simply adjusting the water volume, and the controllable preparation of the ternary heterojunction is realized.

Claims

1. A method for producing an In203-Cu-Cu20 ternary heterojunction catalyst, characterized by, The method comprises the following steps: (1) dispersing indium chloride tetrahydrate in a binary amine alcohol mixed solvent composed of ethylenediamine and ethylene glycol under room temperature and normal pressure, stirring to form a homogeneous solution A; (2) transferring the solution A into a hydrothermal reaction kettle, adding deionized water and Cu2O powder, and sealing to obtain a suspension B; (3) performing a hydrothermal crystallization reaction on the suspension B in the hydrothermal reaction kettle in a vacuum oven, and naturally cooling to obtain a purple suspension C; (4) placing the suspension C into a centrifuge, discarding the supernatant, and then washing the obtained precipitate with water and ethanol alternately for 2-3 times, and then drying in a vacuum oven to obtain a powder-shaped precursor; (5) placing the precursor into a tube furnace for calcination under the protection of an inert atmosphere, and then cooling to obtain the In2O3-Cu-Cu2O ternary heterojunction catalyst.

2. The method of claim 1, wherein, In step (1), the volume ratio of ethylenediamine to ethylene glycol is 1:20-1:30, and the stirring time for forming a homogeneous solution is 20-40 min.

3. The method of claim 2, wherein, In step (2), the volume ratio of added deionized water to ethylenediamine is 80:3-400:

3.

4. The method of claim 1, wherein, In step (3), the hydrothermal crystallization reaction conditions are as follows: 160-200℃ for 10-14 h.

5. The method of claim 1, wherein, In step (4), the centrifugal speed is 4000-6000 rpm, the centrifugal time is 2-5 min, the washing is performed by alternately using deionized water and anhydrous ethanol for 2-3 times, the drying temperature in the vacuum oven is 60℃, and the drying time is 5-7 h.

6. The method of claim 1, wherein, In step (5), the inert gas is nitrogen or argon, the heating rate is 3-5 ℃ / min, the calcination temperature is 600±10℃, the heat preservation calcination time is 3 h, and the furnace is cooled to room temperature after heat preservation. 7.The In 2O 3-Cu-Cu 2O ternary heterojunction catalyst prepared by the preparation method of claim 3, characterized in that, When the volume ratio of deionized water to ethylenediamine is 80:3-160:3, the Cu in the catalyst continuously decreases and the Cu2O gradually increases; when the volume ratio of deionized water to ethylenediamine is 160:3-400:3, the mass fraction of Cu2O in the catalyst is greater than 70%, and tends to be stable.

Citation Information

Patent Citations

  • Preparation method of Cu-Cu2O heterogenous junction

    CN102357659A

  • Cu-Cu2O / Cu2Se photocatalyst and preparation method thereof

    CN117983251A